Fatigue Evaluation of Recycled Asphalt Mixture Based on Energy-Controlled Mode - Tao Ma; Kai Cui; Yongli Zhao; Xiaoming Huang (Advances in Materials Science and Engineering)
The fatigue properties of asphalt mixtures are important inputs for mechanistic-empirical pavement design. To understand the fatigue properties of asphalt mixtures better and to predict the fatigue life of asphalt mixtures more precisely, the energy-controlled test mode was introduced. Based on the implementation theory, the laboratory practice for the energy-controlled mode was realized using a four-point-bending fatigue test with multiple-step loading. In this mode, the fatigue performance of typical AC-20 asphalt specimens with various reclaimed asphalt pavement (RAP) contents was tested and evaluated. Results show that the variation regulation of the dissipated energy and accumulative energy is compatible with the loading control principle, which proves the feasibility of the method. In addition, the fatigue life of the asphalt mixture in the energy-controlled mode was between that for the stress-controlled and strain-controlled modes. The specimen with a higher RAP content has a longer fatigue life and better fatigue performance.